Analysis of Minimum Competency Assessment (MCA) of Student Literacy Skills in Information Text Material for Junior High School Students - Wita Dwi Payana; Rahil Helmi (Faculty of Letters Universitas Balikpapan, 2023)
The purpose of this research is to analyze the reading literacy skills of junior high school students based on the Minimum Competency Assessment (MCA). The participants in this study involved 50 students. The instrument used in the research referred to the types of MCA questions. The method used in this research is quantitative descriptive, which only describes students' literacy skills in information text material without any specific treatment. The research subjects were selected based on cluster random sampling techniques. The data obtained through the research were analyzed with descriptive statistics by determining the average test scores of students to determine the level of students' literacy skills in information text material based on assessment criteria. The research results showed that the reading literacy skills of junior high school students are still in the low category, which is caused by a lack of experience in solving MCA question types, proficiency in information text, educational level, availability of learning resources, teaching methods, and motivation to learn. The low performance of students in reading skills needs to be a special concern, especially by educational institutions, to adjust the implementation of learning that can improve students' reading skills in information text material.